In Vitro Anti-tumor Effects of Photodynamic Therapy on Oral Squamous Cell Carcinoma: A Review - Saberi, Sogol; Hakimiha, Neda; Alaeddini, Mojgan; Etemad-Moghadam, Shahroo; Roudbari, Payam; shahabi, Sima (Journal of Lasers in Medical Sciences, 2022)
Background: Due to the increasing prevalence and high mortality rate of oral cancer and problems of routine treatments, more recent modalities like photodynamic therapy (PDT) have been developed. PDT can effectively destroy tumor cells with minimum side effects. Research on the in vitro effects of PDT may be helpful in determining the molecular mechanisms responsible for its effectiveness, and can lead to development of more efficient techniques. The aim of this study was to review the use of PDT on oral cancer among in-vitro studies. Materials and methods: A literature search for English articles on photodynamic therapy in oral squamous cell carcinoma (SCC) was performed using PubMed, Scopus, Google Scholar, and Web of Science databases. The search string included both MeSH terms and relevant text words. Data extraction was performed based on the inclusion/exclusion criteria. Results: Forty-one studies were selected after reviewing 567 articles. According to the extracted data, the tongue, 5-aminolevulinic acid, viability/cytotoxicity and apoptosis, laser, 600-700nm, were the most common cell-line-source, photosensitizer, assessed outcome, light source, and wavelength respectively used in the studies. Reduced viability and increase apoptosis were the most reported outcomes. Conclusion: PDT showed generally promising effects on reducing the viability of different oral cancer cells. Different cell lines, from various sources or even those originating from the same location, sometimes responded differently to the same protocol. Due to the favorable results obtained from using natural photosensitizers and considering their additional health-promoting properties, their use in future investigations with different cell lines and light specifications is recommended.